Criterion validity of the lower limb isokinetic power-force-velocity profiling parameters in elite athletes - Fessl, I.; Dirnberger, J.; Kröll, J. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to investigate the criterion validity of isokinetic leg press Power-Force-velocity (P-F-v) parameters. Forty elite athletes with diverse sporting backgrounds performed a maximal vertical squat jump test and an isokinetic leg press P-F-v profile test. The isokinetic leg press P-F-v profile consisted of leg-extension against 4 given velocity conditions: 0.1, 0.3, 0.7, and 1.2 m/s. Criterion validity was evaluated using correlation between squat jump height and each isokinetic P-F-v parameter (F0, v0, Pmax and, Sfv). Nearly "good" (r > 0.815) correlations were found for Pmax, whereas correlations between the remaining P-F-v parameters ranged from "poor" to "impractical" (r = 0.702- 0.159). This result may fit the previous assumption of P-F-v profiles, that individuals express variable contributions of F0 and v0 for similar Pmax values. Consequently evaluating criterion validity for these parameters (F0 and v0) is likely difficult would be contrary to this P-F-v assumption.